2018
DOI: 10.1177/0081246318807800
|View full text |Cite
|
Sign up to set email alerts
|

Do congruent apologies facilitate forgiveness?

Abstract: Research largely supports the apology–forgiveness cycle, a process in which perpetrators’ post-transgression apologies are reciprocated with victims’ forgiveness. This cycle is often facilitated by the mere provision of an apology. Yet, there are times in which apologies may be rejected. We hypothesised that when apologies matched victims’ apology preferences (i.e., congruent apologies), victims would be more likely to accept them and self-report higher levels of forgiveness. Using an autobiographical transgre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The measure consists of 18 items that capture motivations (i.e., revenge, avoidance, benevolence) theorized to underlie forgiveness (or a lack thereof). Similar to prior studies (e.g., Cowden et al, 2019a), we derived a composite index corresponding with state forgiveness by aggregating responses to each item after reverse scoring the items from the revenge and avoidance subscales.…”
Section: Methodsmentioning
confidence: 99%
“…The measure consists of 18 items that capture motivations (i.e., revenge, avoidance, benevolence) theorized to underlie forgiveness (or a lack thereof). Similar to prior studies (e.g., Cowden et al, 2019a), we derived a composite index corresponding with state forgiveness by aggregating responses to each item after reverse scoring the items from the revenge and avoidance subscales.…”
Section: Methodsmentioning
confidence: 99%
“…That is, just as ‘apology’ is not a neutral word’ (Kerstens, 2008: 188), so too ‘forgiveness’ is strongly encoded with emotional connotations. Such ‘congruent apologies’ (Cowden et al, 2019), which correspond with victims/survivors’ needs and sentiments, have a higher capacity to generate forgiveness and thus appear to be integral to the apology–forgiveness cycle. In other words, while official public apologies by church or state are often subject to ‘sanitizing’ and depersonalized and ‘distancing’ processes by lawyers or advisers as suggested above, ultimately it is the overtly human and personal elements of intergroup apologies which work towards establishing both a connection to the wrongdoing and authenticity for victims/survivors.…”
Section: Part Iv: Concluding Thoughtsmentioning
confidence: 99%
“…In cases where an apology precedes forgiveness in the apology-forgiveness cycle, central to this cycle may be that the apology matches the needs of victims. This is demonstrated by research by Cowden et al (2019). To examine what kind of an apology may facilitate forgiveness, they asked participants to recall a past transgression they experienced and evaluate the apology offered by their transgressor.…”
Section: Key Elementsmentioning
confidence: 99%
“…To examine what kind of an apology may facilitate forgiveness, they asked participants to recall a past transgression they experienced and evaluate the apology offered by their transgressor. Their findings revealed that the apology that was congruent with the ‘victims’ preferences for empathy, compensation, and acknowledgement of violated norms’ was more likely to promote forgiveness among victims (Cowden et al, 2019: 411). Since an apology has a variety of components such as taking responsibility, this finding leads to a question as to how offenders should apologise in a way that is consistent with the victims’ needs.…”
Section: Key Elements and Impediments Of Apology–forgiveness Cycle In...mentioning
confidence: 99%